Pulgão Melanaphis sorghi (Theobald, 1904) (Hemiptera: Aphididae) na cultura do sorgo: análise do cenário brasileiro - Avellar, Guilherme S.; Marriel, Ivanildo E.; Menezes, Cicero B.; Santos, Douglas G.; Santos, Nathan M.; Mendes, Simone M. (Entomological Communications, 2023)
From the 2018/2019 agricultural season, reports of the occurrence of a new pest in the sorghum crop began in Minas Gerais and São Paulo, where abundant infestations of the aphid Melanaphis sorghi (Theobald, 1904) (Hemiptera: Aphididae) in crops with negative impacts on the yield of grains, causing losses to producers. Thus, this work aimed to evaluate the occurrence and scenario of the infestation of this pest in the sorghum crop in the country, aiming to understand its dynamics and support strategies for its management. As a data collection technique, a controlled electronic control was used, made available through the google forms digital platform, for 90 days, to the various actors of agribusiness, linked to the sorghum culture of different extracts of producers, throughout the country. Containing 14 questions related to knowledge of the crop, cultivated area, use of agrochemicals and occurrence of the pest. The greatest losses observed reached values of up to 20% of production. Of the total number of preparations, 64% used some chemical product, 42% using it with their own knowledge, 29% using it under the prescription/recommendation of a professional and 29% did not use pesticides. There was wide dissemination of the sorghum aphid in sorghum crops in the country, which implies necessary control measures in order to reduce losses, according to the profile of the evaluated producers.